A BRIEF VIEW ON BILINGUAL SCHOOLS IN THE CAPITAL OF INDONESIA - Annas Surdyanto (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTThis study aimed at providing the portraits of bilingual schools in the capital of Indonesia and critically revealing the Ministry of Culture and Education policy on bilingual schools. This study employed a qualitative case design and took place at 5 bilingual schools. The data were taken with semi-structure interview, school document, observation and related literature. There were 10 teachers participating. This study showed descriptions of bilingual schools regarding the curriculum, the teaching and learning activity, the assessment, the accessibility, the teachers, the students, and the role of environment. The data derived were then analyzed and used to evaluate the government policy on bilingual schools related to the process of teaching and learning as well as its assessment. The analysis and evaluation found out some missing alignments between the policy and bilingual school principles. They were uncontrolled curriculum development as a combination of international and national curriculum, the Teacher Training Program provided by the government (PLPG) towards bilingual school teachers, and the establishment of standardized test. This study suggested that there must be an education council specialized for bilingual schools that concerns on designing the framework of school-based curriculum development (SBCD), teacher training program and standardized test establishment for bilingual schools. ABSTRAKPenelitian ini bertujuan untuk menyediakan potret sekolah bilingual di ibukota Indonesia dan mengungkapkan kebijakan Kementerian Pendidikan dan Kebudayaan di sekolah bilingual secara kritis. Penelitian ini menggunakan desain kasus kualitatif dan berlangsung di lima sekolah bilingual. Data diambil dengan wawancara semi-struktur, dokumen sekolah, observasi dan literatur terkait. Ada 10 guru yang berpartisipasi. Penelitian ini menunjukkan deskripsi sekolah bilingual mengenai kurikulum, kegiatan belajar mengajar, penilaian, aksesibilitas, guru, siswa, dan peran lingkungan. Data yang diperoleh kemudian dianalisis dan digunakan untuk mengevaluasi kebijakan pemerintah pada sekolah bilingual yang terkait dengan proses pengajaran dan pembelajaran serta penilaiannya. Analisis dan evaluasi menemukan beberapa keberpihakan yang hilang antara kebijakan dan prinsip sekolah bilingual. Mereka adalah pengembangan kurikulum yang tidak terkendali sebagai kombinasi kurikulum internasional dan nasional, Program Pelatihan Guru yang disediakan oleh pemerintah (PLPG) terhadap guru sekolah dwibahasa, dan pembentukan tes standar. Studi ini menyarankan bahwa harus ada dewan pendidikan khusus untuk sekolah bilingual yang berkaitan dengan merancang kerangka pengembangan kurikulum berbasis sekolah (SBCD), program pelatihan guru dan pendirian tes standar untuk sekolah bilingual.  How to Cite: Surdyanto, A.. (2018). A Brief View on Bilingual Schools in the Capital of Indonesia. IJEE (Indonesian Journal of English Education), 5(1), 1-15. doi:10.15408/ijee.v5i1.8018